2012
DOI: 10.13066/kspm.2012.7.3.251
|View full text |Cite
|
Sign up to set email alerts
|

Comparision of the Muscle Activity and Balance of Lower Extremities in Exercise Using TOGU on the Unstable Surface and Stable Surface after Reconstruction of the ACL

Abstract: Purpose The purpose of this study is to provide an efficient and basis for muscle activity of Quadriceps muscles and balance in anterior cruciate ligament reconstruction patients through unstable surface exercise and stable surface exercise. Methods This study included 30 anterior cruciate ligament reconstruction patients belonging to A hospital and D orthopedic surgery clinic of province who attended the program for 30 minutes at a time and three times a week for 4 weeks. Of these 15 attended the unstable sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Seo and Kim 17 ) demonstrated that the muscle activation ratios of the rectus femoris and biceps femoris were higher on an unstable surface than on a stable surface, in their balance training on 60 stroke patients. Lim 18 ) conducted exercise training in two groups, namely an unstable surface group and a stable surface group, in 30 patients who had undergone anterior cruciate ligament reconstruction. Both groups showed significantly higher muscle activities of the vastus medialis and the VL; however, the muscle activity was higher in the unstable surface group.…”
Section: Discussionmentioning
confidence: 99%
“…Seo and Kim 17 ) demonstrated that the muscle activation ratios of the rectus femoris and biceps femoris were higher on an unstable surface than on a stable surface, in their balance training on 60 stroke patients. Lim 18 ) conducted exercise training in two groups, namely an unstable surface group and a stable surface group, in 30 patients who had undergone anterior cruciate ligament reconstruction. Both groups showed significantly higher muscle activities of the vastus medialis and the VL; however, the muscle activity was higher in the unstable surface group.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, exercise therapy schemes that use small tools for the neck have received increasing attention; a sling, a TOGU, a gym ball, a foam roller, and a biofeedback stabilizer are mainly used. These somesthesia-motor training tools are proven to be effective in improving posture control (Lim, 2012). Since these exercises are performed on a trembling surface, they awaken the brain by activating the proprioceptive receptors to quicken information processing speed, which improves physical agility and power as well as coordination power.…”
mentioning
confidence: 99%